2019
DOI: 10.1111/mcn.12764
|View full text |Cite
|
Sign up to set email alerts
|

High proportions of children under 3 years of age consume commercially produced snack foods and sugar‐sweetened beverages in Bandung City, Indonesia

Abstract: Child undernutrition continues to be a national concern in Indonesia, whereas childhood overweight/obesity rises. Economic development has led to wide availability of highly processed foods and beverages, with growing evidence that children are consuming commercial snack products during the critical complementary feeding period. This study assessed the prevalence and patterns of consumption of commercially produced snack foods and sugar‐sweetened beverages among Indonesian children. A cross‐sectional survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 47 publications
2
33
1
2
Order By: Relevance
“…The most prevalent caregiver‐targeted promotion was for sweetened milks (22.3%), which is also troubling as a recent multi‐country study on the perception of beverage healthiness found that Indonesian participants perceived flavoured, sweetened milk to be healthier than other sugar‐sweetened beverages (Thomson et al, ). With prevalent consumption of unhealthy commercial snack products by young children in Indonesia (Green et al, ), and rising rates of child overweight/obesity (MOH, ; Rachmi, Li, & Baur, ), promotions for these products could have a significant impact on the health and well‐being of children in Indonesia. The Indonesian government should consider passing and enforcing food industry regulations related to caregiver‐ and child‐targeted promotion of commercial snack foods to reduce the impact of unhealthy snacking among children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most prevalent caregiver‐targeted promotion was for sweetened milks (22.3%), which is also troubling as a recent multi‐country study on the perception of beverage healthiness found that Indonesian participants perceived flavoured, sweetened milk to be healthier than other sugar‐sweetened beverages (Thomson et al, ). With prevalent consumption of unhealthy commercial snack products by young children in Indonesia (Green et al, ), and rising rates of child overweight/obesity (MOH, ; Rachmi, Li, & Baur, ), promotions for these products could have a significant impact on the health and well‐being of children in Indonesia. The Indonesian government should consider passing and enforcing food industry regulations related to caregiver‐ and child‐targeted promotion of commercial snack foods to reduce the impact of unhealthy snacking among children.…”
Section: Discussionmentioning
confidence: 99%
“…Small stores were sampled for their proximity to public sector health facilities offering child health services (WHO & UNICEF, ). The 33 facilities were identified in coordination with the Bandung City Health Office in preparation for a survey with mothers of young children (Green et al, ). Using Google Maps and Google Street View, four small stores in closest proximity to each health facility were listed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Green et al () report on consumption patterns among 495 children 6–35 months of age interviewed as part of a cross‐sectional survey in Bandung City. Consumption of commercial infant and young child feeding products was prevalent, with 49.5% and 37.4% of children having consumed a BMS or commercially produced complementary food in the previous day.…”
Section: Generating New Data On Commercial Snack Food Consumption: Prmentioning
confidence: 99%
“…This study was conducted as a substudy of an assessment of availability and promotions of CPCF in Bandung City, Indonesia, in 2017 (Green et al, ). CPCF were defined as foods recommended for children less than 3 years of age with a label or package that recommends an age of introduction less than 3 years on the label and/or uses the term “baby” or words referring to a child's age to describe the food (e.g., “baby food”), not including infant formula or other breastmilk substitutes (WHO, ).…”
Section: Methodsmentioning
confidence: 99%